Ukuran Perusahaan Sebagai Pemoderasi Pengaruh ESG, Profitabilitas, Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan (Studi Perusahaan Manufaktur yang Terdaftar di BEI 2019-2023) - Mursalina, Mursalina; Mardani, Ronny Malavia; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study uses company size as a moderating variable to examine how ESG, profitability, and company growth affect company value. This sample was taken using a saturated sample technique with a research period from 2019-2023, so that a total sample of 65 data was obtained. SEM-PLS is used in the data analysis procedure. The software used WrapPLS 7.0. The findings demonstrared that while profitability has a significant positive impact on firm value, ESG has a significant negative impact. Company growth has a negative but insignificant impack on firm value, and company size can moderate the relationship between profitability on firm value but not the relationship between ESG and company growth. Keywords: Environmental, Social, Governance, Profitability, Firm Growth, Firm Value, Firm Size